TINDAKAN INTRANSPARANSI DIREKSI DALAM RAPAT UMUM PEMEGANG SAHAM TERHADAP PARA PEMEGANG SAHAM (STUDI KASUS PT. SUMALINDO LESTARI JAYA, TBK) - Tsusayya Dhiya Prabowo (2022)
The Board of Directors is an organ that plays an important role in determining the progress of a company. The importance of the position of the board of directors is reflected in the duties and responsibilities attached to it, as formulated in the Company Law. The existence of the GMS is the highest organ that has certain powers and the obligation of the board of directors to seek approval from the GMS in carrying out certain actions is considered an adequate form of protection for shareholders and creditors. Every action taken by the board of directors must be accounted for in the GMS. The purpose of this study was to determine the form of legal protection of the shareholders against the transparency of buying and selling shares by the directors and the form of law enforcement and accountability of the directors who carried out the transparency of the sale and purchase of shares to the shareholders. The research used in this paper is normative legal research which is based on reviewing the literature, laws and regulations, applicable legal theory. The result of this research is that legal protection for shareholders is not given fairly, not honest, and not transparent. The form of legal protection of shareholders against the transparency of buying and selling shares carried out by the board of directors has also been stated in the Articles of the Company Law, including personal interests and the interests of the company so as not to be cheated by company activities which ultimately cause various losses to many parties.